Epicardial adipose tissue, infarct size, microvascular obstruction and ventricular remodelling after ST-segment elevation myocardial infarction. (3rd October 2022) - Aimo, A; Gavara, J; Lopez-Lereu, M P; Monmeneu, J V; De Dios, E; Perez-Sole, N; Marcos-Garces, V; Rios-Navarro, C; Emdin, M; Lupon, J; Bayes-Genis, A; Bodi, V
Abstract: Background: Epicardial adipose tissue (EAT) is a biologically active fat deposit contained beneath the pericardium promoting coronary atherosclerosis. EAT can be accurately measured through cardiac magnetic resonance (CMR), which also enables an accurate quantification of infarct size, microvascular obstruction (MVO), left ventricular (LV) ejection fraction (EF) and volumes in patients with ST-elevation myocardial infarction (STEMI). Purpose: We performed a systematic assessment of the correlates of EAT volume at baseline and after 6 months in a homogeneous cohort of patients with STEMI. Methods: We prospectively enrolled patients with a first anterior STEMI reperfused within 12 hours from symptom onset. These patients underwent a first CMR exam after 1 week from the MI and after 6 months. Results: Patients (n=138) were more often men (81%), with a median age of 58 years (interquartile range 48–66). EAT volume was 30 mL/m 2 (23–41). Patients with EAT >30 mL/m 2 (n=69) were older (60±12 vs. 55±11 years, p=0.02), more often diabetic (26% vs. 12%, p=0.03), and showed a worse baseline risk profile (Thrombolysis in Myocardial Infarction risk score 3 [2–5] vs. 2 [1–4], p=0.05). Patients with EAT >30 mL/m 2 also displayed a larger IS (33±15 vs. 23±16% of LV mass, p=0.001) and MVO (1.5 [0–6.8] vs. 0% [0–2.2], p=0.008). Again in patients with EAT >30 mL/m 2, EAT volume independently predicted infarct size (standardized beta coefficient=0.30, p<0.001) and MVO area (standardized beta coefficient=0.36, p<0.001) after adjusting for age, sex and infarct characteristics at 1 week (Figure 1). Despite these correlations with infarct size and MVO, patients with EAT >30 mL/m 2 did not display more depressed LVEF or larger LV volumes than those with EAT ≤30 mL/m 2, either at 1 week or at 6-month CMR (p>0.1 for all comparisons). Conclusions: In a cohort of patients with first anterior STEMI undergoing timely reperfusion, those with a greater EAT volume have a larger infarct size and a larger area of MVO. Despite these correlates of EAT volume size, patients with larger EAT do not have a higher risk of adverse LV remodelling. Funding Acknowledgement: Type of funding sources: None.